2020
DOI: 10.1177/0300891620979358
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative complications after minimally invasive esophagectomy in the prone position: any anesthesia-related factor?

Abstract: Objective: To evaluate the incidence of postoperative complications arising within 30 days of minimally invasive esophagectomy in the prone position with total lung ventilation and their relationship with 30-day and 1-year mortality. Secondary outcomes included possible anesthesia-related factors linked to the development of complications. Methods: The study is a retrospective single-center observational study at the Anesthesia and Surgical Department of a tertiary care center in the northeast of Italy. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“… 32 , 33 A recent retrospective study found that blood cell transfusion has an OR of 2.02 for the development of postoperative complications in patients undergoing MIE. 34 In the present study, the PPCs group also had higher incidences of non-pulmonary complications than the non-PPCs group. Therefore, it is unclear whether the risk of development of PPCs was caused by transfusion or was related to a higher incidence of non-pulmonary complications.…”
Section: Discussionsupporting
confidence: 51%
“… 32 , 33 A recent retrospective study found that blood cell transfusion has an OR of 2.02 for the development of postoperative complications in patients undergoing MIE. 34 In the present study, the PPCs group also had higher incidences of non-pulmonary complications than the non-PPCs group. Therefore, it is unclear whether the risk of development of PPCs was caused by transfusion or was related to a higher incidence of non-pulmonary complications.…”
Section: Discussionsupporting
confidence: 51%
“…More evidence is needed in this regard. Evidence highlights that postoperative complication worsens patient outcomes ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the specific surgical program, the patient's position (supine, lateral decubitus or prone) and the type of surgery (with or without a thoracotomy), two principal aspects need to be taken into account. First, we know that an intraoperative fluid volume >4 litres and higher fluid balances on post-operative day 1 are independent risks factors for PPCs, with a 16% increase in the risk of postoperative symptoms for each additional litre and a 32% increase in the probability of PPCs after esophagectomy (71)(72)(73). Second, the restrictive fluid approach should not be translated as tout court in this type of surgery.…”
Section: Fluids and Hemodynamicmentioning
confidence: 99%
“…So, transfusions are rarely needed nowadays (93). In addition, various studies have demonstrated that perioperative red blood cell (RBC) transfusions are associated with more postoperative complications and a higher risk of death after esophagectomy (71,94,95). RBC administration is only advisable for Hb levels <7 g/dL in the absence of cardiac disease and with normal organ perfusion parameters (lactate levels within normal range, adequate urine output, normal S c VO 2 and hemodynamic stability).…”
Section: Blood Products Transfusionmentioning
confidence: 99%